Architecture of network knowledge base of a complex military system - Yermoshyn, M.; Poberezhnyi, A.; Onopriyenko, O.; Shuryha, M. (Radiotekhnika, 2021)
The article examines the architecture of a networked knowledge base and the organizational structure of a complex military-purpose system, which is built when a group of troops (forces) is created and kept in a state where it is capable of solving the tasks assigned to it. This requires a deep study of issues not only of modern tactics regarding the preparation and conduct of hostilities, but also more complex issues of scientific substantiation of the architecture of a networked knowledge base and the structure of a complex military system with a networked knowledge base. The internal representation of knowledge in the knowledge base (formal programmatic and logical content) is advisable to implement in the form of an adjacency matrix, which displays the relationship and relationship between target settings; initial conditions; the resources of the grouping of troops (temporary, material, combat and quantitative composition), their costs and replenishment; rules for the use of resources and the choice of criteria for their distribution. The knowledge base synthesizes a mathematical network model for making decisions, which provides a change (correction) of the structure of target attitudes when replenishing the knowledge base. Tasks solved in the knowledge base: selection of vertices and relations when replenishing catalogs; making changes to the adjacency matrix in accordance with the identified or changed relationships between targets. A necessary element of the synthesis of a mathematical network model for making decisions on the preparation and conduct of hostilities is the construction of the structure of the target systems of the system for a specific situation. A feature of controlling the correctness of knowledge presented in the form of target attitudes is the need for a joint analysis of the entire set of target attitudes and initial conditions in their relationship. For this, the matrix of the relations of target attitudes and the matrix of the relations of initial conditions are combined. The control of the correctness of the knowledge base is carried out when replenishing the knowledge base, it includes: identification of contradictions in the structure of target attitudes when making changes to this structure; search and detection of contradictions in the graph of the semantic network according to available resources and time; checking the completeness of the graph of the mathematical network model; issuance of revealed contradictions to an expert and their elimination. A practical approach to building the architecture of a networked knowledge base and the organizational structure of a complex military system can be implemented during the substantiation of the components and elements of the system when creating a grouping of troops (forces).